Submental island flap reconstruction reduces cost in oral cancer reconstruction compared to radial forearm free flap reconstruction: a case series and cost analysis. Issue 1 (December 2016) - Forner, D.; Phillips, T.; Rigby, M.; Hart, R.; Taylor, M.; Trites, J.
Abstract Background In Canada, 4, 400 cases of oral cancer are diagnosed yearly. Surgical resection is a key component of treatment in many of these cancers. Reconstruction of defects, with the goal of preserving function, is of utmost importance. Several choices are possible for reconstruction of larger defects, including both free and pedicled flaps. Free flap reconstruction is reliable and effective, but requires additional personnel and peri-operative resources. Pedicled flaps remain an important alternative to free flaps, and are less resource intensive. This paper reviews our inaugural experience with the submental island flap (SIF) and compares costs incurred to a matched cohort of oral cancer patients reconstructed with forearm free flaps. Methods Charts of patients who underwent SIF and RFFF reconstruction from January 1st 2013 to April 1st 2015 were retrospectively examined. Associated costs were obtained via online database and previously reported costs at the study institution. Results Mean length of ICU stay in glossectomy RFFF reconstruction was 4.7 days. Only one patient required ICU stay for one night in the SIF group. Mean length of hospital stay was not significantly different in SIF patients vs RFFF patients (12.4 vs 15.4 days, p > 0.05). Mean operative time was significantly lower in the SIF group compared to the RFFF group (347 vs 552 min, p < 0.05). Total mean intraoperative costs were found to be 4780.59 for RFFF operations, versus 2307.94 for SIF. Total mean cost of post-operative stay was 18158.40 in the SIF group and 43617.60 in the RFFF group. Total cost savings were therefore 27931.85 per patient for the SIF group. Conclusions We have demonstrated the use of the submental island flap as an alternative to radial forearm free flaps, showing both decreased hospital costs and comparable patient outcomes. Pedicled flaps are making a resurgence in head and neck reconstruction, and the submental island flap offers an excellent alternative to more labour intensive and costly free flap alternatives.